Implementation of Experiential Learning Theory in Islamic Religious Education during Covid-19 Pandemic - Evita Nur Apriliana; Ulya Barokati Tamami; Agus Sutiyono (DAYAH: Journal of Islamic Education, 2022)
The purpose of this study is to demonstrate how experiential learning theory was applied in Islamic religious education during the covid-19 epidemic. Interviews and observations are used to acquire primary data, whereas documentation studies obtain secondary data. This research was conducted at SMP Takhassus Al-Qur'an Tarub Tegal and SMA N 1 Karanggede, Boyolali. The data validity test is accomplished by triangulating the data analysis sources utilizing Miles and Huberman analysis, which consists of three stages: data reduction, data visualization, and data verification. The findings indicated that experiential learning theory might be applied to pandemic education in four stages: tangible experience, reflective observation, abstract conceptualization, and active experimentation, both offline and online learning. Experience-based Islamic religious education helps students learn, comprehend, live, and practice Islamic teachings.